Peran Legislator Dalam Perubahan Peraturan Daerah - Kuswan Hadji; Muhammad Razaq firdaus; Muhamad Wisnu Haikal; Vinky Wahyu Anjas Prianggoro; Narendra Dzaki Dwitanaya; Andika Ivan Putra Pamungkas (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This paper examines the evolution of regional governance in Indonesia since the reform era, beginning with the replacement of Law Number 5 of 1974 by Law Number 22 of 1999, and its subsequent revision into Law Number 32 of 2004. These legal reforms reflect the nation's efforts to balance centralization and decentralization, with the principle of checks and balances as a foundational element. The article highlights the central role of the Regional People's Representative Council (DPRD) in the formation of regional regulations (Perda), oversight functions, and budget determination. Through literature research, this paper demonstrates that the DPRD holds strategic authority in regional legislation, involving the planning, drafting, discussion, and ratification of Perda. In conclusion, the DPRD plays a crucial role in establishing a democratic and accountable regional governance system in Indonesia.